(untitled) (Journal of Medical & Health Sciences Review, 2025)
Stuttering is a multifaceted communication disorder involving speech motor control, linguistic processing, and emotional experience. Despite advances in theory and treatment approaches, many newly qualified speech-language pathologists report difficulty applying academic knowledge to real-world clinical contexts. This challenge often reflects a gap between how stuttering is taught and how it manifests in the lived experiences of people who stutter. Drawing on clinical and educational experience, this article examines common pedagogical approaches to stuttering, identifies areas where students struggle during clinical training, and argues for a more integrated teaching framework. Emphasis is placed on moving beyond technique-centered instruction toward an approach that incorporates linguistic load, counseling skills, and client-centered communication. Implications for speech-language pathology education and clinical training are discussed.